Theoretical study of the dissociative photodetachment dynamics of the hydrated superoxide anion cluster. Issue 31 (2nd August 2021) - Hashimoto, Yu; Saito, Kohei; Takayanagi, Toshiyuki; Tachikawa, Hiroto
Abstract : Theoretical calculations that can account for nuclear quantum effects were carried out to interpret the experimentally-measured photoelectron spectra of the O2 − ·H2 O anion complex. Abstract : The dissociative photodetachment of the hydrated superoxide anion cluster, O2 − ·H2 O + hν → O2 + H2 O + e −, is theoretically investigated using path-integral and ring-polymer molecular dynamics simulation methods, which can account for nuclear quantum effects. Full-dimensional potential energy surfaces for the anionic and lowest two neutral states (triplet and singlet spin states) are constructed based on extensive density-functional theory calculations. The calculated photoelectron spectrum agrees well with the experimental spectra measured for different photodetachment laser wavelengths. The calculated photoelectron–photofragment kinetic energy correlation spectrum also agrees well with previous experimental measurements. The dissociation mechanisms, including available energy partitioning and the importance of nuclear quantum effects in photodetachment, are discussed in detail.